Unit-level Explanation on Indonesian Foreign Policy - Miftachul Choir (Journal Of Global Strategic Studies, 2021)
Neo-realism predicted the state will choose a certain balancing strategy accordingly to the given strategic environment and the relative power of respective states. Since Southeast Asia recognized as informal and norm-based regionalism, state balancing strategy will maximize the regional organization as a means to restraining member state's behavior and managing basic interaction within states. However, neo-realism unable to explain why states would not adopting the expected balancing strategy despite already obtained necessary international pressure and relative power. This condition occurred in Indonesia’s foreign policy toward ASEAN, especially on combating illegal fishing disputes. Ever since the foundation of the regional group, Indonesia has applied the ASEAN-led mechanism as a means to the dispute. However, the regional distribution of power and Jakarta’s relative power do not change but Indonesia’s balancing strategy does. To explain such conditions, this research will employ neo-classical realism to examine why Indonesia not adopting an institutional balancing strategy. Neoclassical-realist argued that it is the intervening variable that determined the state’s balancing strategy. This research will analyze Indonesia’s intervening variable using Randall Scwheller’s elite consensus framework and found out the shift of Indonesia's balancing strategy occurred due to elite dissensus on how perceiving ASEAN as a regional group